1694 Mass. Acts 12 - (:unkn) unknown (My University, 1694)
No. 6, An Act for the Punishing of Criminal Offenders: Further it is Enacted by the authority aforesaid, That every Justice of the Peace in the County where the Offence is committed , may cause to be staid and arrested all Affrayers, Rioters, Disturbers, or Breakers of the Peace, and such as shall ride or go armed Offensively before any of their Majesties Justices, or other Their Officers or Ministers doing their Office or elsewhere.
Keywords: GOING ARMED